Modification of (DGEBA) epoxy resin with maleated depolymerised natural rubber (eXPRESS Polymer Letters)
In this work, diglycidyl ether of bisphenol A (DEGBA) type epoxy resin has been modified with maleated depolymerised natural rubber (MDPR). MDPR was prepared by grafting maleic anhydride onto depolymerised natural rubber. MDPR has been characterized by Fourier transform infrared (FT-IR) spectroscopy and nuclear magnetic resonance spectroscopy. MDPR was blended with epoxy resin at three different ratios (97/3, 98/2 and 99/1), by keeping the epoxy resin component as the major phase and maleated depolymerised natural rubber component as the minor phase. The reaction between the two blend components took place between the acid/anhydride group in the MDPR and the epoxide group of the epoxy resin. The proposed reaction schemes were supported by the FT-IR spectrum of the uncured Epoxy/MDPR blends. The neat epoxy resin and Epoxy/MDPR blends were cured by methylene dianiline (DDM) at 100°C for three hours. Thermal, morphological and mechanical properties of the neat epoxy and the blends were investigated. Free volume studies of the cured, neat epoxy and Epoxy/MDPR blends were correlated with the morphological and mechanical properties of the same systems using Positron Annihilation Lifetime Studies.